Profitability Analysis of Tiger Grouper Hatchery (Epinephelus fuscoguttatus) Household Scale in Kelatakan Village, Situbondo, East Java - Mustika Palupi; Ren Fitriadi; Muh Sulaiman Dadiono; Danang Yonarta; Rima Oktavia Kusuma (Journal of Aquaculture and Fish Health, 2021)
The development of tiger grouper cultivation technology has not been maximally implemented so that the survival rate of fish is very low. The result is that it is very vulnerable to losses in cultivation. This study aims to analyze the profitability of tiger grouper hatchery. The research method used is a case study. Primary data is collected through observation, interviews, and questionnaires. Secondary data is data obtained indirectly. The calculated data analysis is the Benefit-Cost (B/C) Ratio, Break-even Point Analysis and Profitability. The results obtained are BEP in units is 170,606 heads and BEP in price is IDR 1,709,750, B/C Ratio is 1.65, and the payback period is 5 years 2 months.